Potential of Cassava Clones for Iron, Zinc, and Selenium Biofortification - Karini Aparecida Matos Inacio; Nancy Carrasco Farfan; Carlos Eduardo Xisto Azevedo; Marco Antônio Gomes Polatto; Natã Souza Carrion; Polliany Vitória Santos Mendes; Nikolas Souza Mateus; Elcio Ferreira Santos (Agriculture, 2024)
Cassava (Manihot esculenta Crantz) is a crucial staple food in South America, providing starchy storage roots that contribute to the sustenance of millions. To address deficiencies in iron (Fe), zinc (Zn), and selenium (Se), a global initiative is underway to identify plant species and genotypes that naturally accumulate these nutrients for human consumption, such as cassava. In this way, this study aims to identify potential cassava genotypes for biofortification in Fe, Zn, and Se, while also improving the overall cassava yield. We evaluated the accumulation potential of Fe, Zn, and Se in 20 South American cassava genotypes under traditional growing conditions, concurrently examining their photosynthetic and growth characteristics. Cassava roots exhibited Zn content ranging from 3.20 to 8.56 mg kg−1, Fe content from 2.20 to 10.73 mg kg−1, and Se content from 1.20 to 9.43 µg kg−1 (expressed on a dry basis). Genotypes MS018, DG014, and DG839 emerged as promising candidates for biofortification programs, displaying elevated levels of Fe, Zn, and Se, coupled with superior photosynthetic capacity. These genotypes, recommended for biofortification programs, also demonstrated increased yield potential. The findings from this study contribute to the development of cassava genotypes with enhanced agronomic biofortification and elevated yield potential.